If you ask me - Hubscher, Libby (Jove, 2022)
"When an advice columnist's picture-perfect life implodes, she opts to go rogue in this hilarious, heartwarming romance from the author of Meet Me in Paradise. Violet Covington pens Dear Sweetie, the most popular advice column in the state of North Carolina. She has an answer for how to politely handle any difficult situation...until she discovers her husband, Sam, has been cheating on her. Furious and out of sensible solutions, Violet leaves her filter at the door and turns to her column to air her own frustrations. The new, brutally honest Dear Sweetie goes viral, sending more shock waves through Violet's life. When she burns Sam's belongings in a front-yard, late-night bonfire, a smoking-hot firefighter named Dez shows up to douse the flames, and an unexpected fling quickly shows potential to become something longer lasting. A lot of people want to see the old polished Violet return-including her boss, who finds her unpredictability hard to manage, and Sam, who's begging for another chance. But Dez appreciates Violet just the way she is-in fact, he can't get enough of her. The right answers don't come easily when Violet finds herself at her own personal crossroads. But maybe, by getting real, Violet can write her own happy ending"--